Cálculo funcional associado a problemas com condições dinâmicas de contorno - Dalcy, Muriel Andreane (Universidade Federal de São Carlos, 2025)
This work aims to study the holomorphic functional calculus associated with a problem with dynamic boundary conditions defined on $\Omega$, where $\Omega \subset \mathbb{R}^n$ is a bounded and connected open set with $C^\infty$ boundary $\Gamma = \partial \Omega$. Our main goal is to show that the sectorial operator associated with this problem has a bounded $H_\infty$ functional calculus and, for this purpose, we will utilize tools from the Boutet de Monvel calculus, as well as concepts from Functional Analysis.
Functional calculus associated with problems with dynamic boundary conditions
Keywords: Cálculo funcional; Problemas de contorno; Equações parabólicas; Operadores pseudodiferenciais; Boutet de Monvel; Functional calculus; Boundary value problem; Parabolic equations; Pseudo-differential operators; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ANALISE::EQUACOES DIFERENCIAIS PARCIAIS